Modernization of Agriculture and Use of Information and Communication Technologies by Farmers in Coastal Yogyakarta - Dyah Woro Untari; Ratih Ineke Wati; Gagar Mewasdinta; Subejo Subejo (Indonesian Journal of Geography, 2019)
In the development process, Information and Communication Technologies (ICTs), which also commonly referred to as electronic media or cyber media have been acknowledged as a new instrument that could facilitate the need of new information and innovation for rural people or farmers. However, several studies reported that extension and communication based-electronic media in developing countries encounter more problems rather than in developed countries. This research aims to investigate the ownership, access, utilization or functions of ICTs for obtaining information supporting the daily life of farmers and for promoting various farming activities in the coastal area of Kulon Progo Regency Yogyakarta. The research method of the study was a descriptive method that has been conducted by a mixed method. The study found that in line with modernization in agriculture, farmers have been using conventional and new electronic media including television, radio and mobile phone with function for getting new information. Conventional electronic media are still dominant while the use of new electronic media has been gradually increasing. Information gathered from ICTs includes social, cultural, economic, health and environmental issues. The use of new electronic media particularly the internet via smartphone has newly started to be utilized among farmers in the coastal farming area who intensively engaged in horticulture crops cultivation mainly for getting and exchange the market information. Information on technological innovation is still dominant among farmers. Better infrastructure and mobility access, improvement of telecommunication network and development of content and format of information provided by new media will be prospective in the future